2017
DOI: 10.1002/bmc.4028
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic comparison of two phenolic acids after oral administration of Typhae pollen to normal rats and rats with acute cold blood stasis

Abstract: Typhae Pollen, dried pollen of Typha angustifolia L., Typha orientalis Presl or other plants of the same genus (Typhaeceae), has the effect of activating the circulation to cure blood stasis in traditional Chinese Medicine. The purpose of this study was to set up an ultra-high performance liquid chromatography method that could determine p-hydroxybenzoic acid and vanillic acid simultaneously in rat plasma, and to compare their pharmacokinetics in normal rats and rats with acute cold blood stasis, and further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Oxygen and glucose deprivation (OGD) is a well-established in vitro model in studying the pathology and pharmacology of ischemic damage (Gu et al, 2013;Guo et al, 2013;Morán et al, 2017;Tian et al, 2020). Considering the actual clinical situations, patients usually take medications of XXMD in the poststroke (Pan et al, 2017;Zhong et al, 2020); we study the effect of components in treating stroke-based PC12 cells in the case that cells were protected with components after OGD. During the OGD, the cells were incubated in the culture medium without FBS in a hypoxic bag at 0.1% O 2 , 5% CO 2 , and 37 °C for 18 h (Gu et al, 2013;Morán et al, 2017).…”
Section: Oxygen and Glucose Deprivation Protocolmentioning
confidence: 99%
“…Oxygen and glucose deprivation (OGD) is a well-established in vitro model in studying the pathology and pharmacology of ischemic damage (Gu et al, 2013;Guo et al, 2013;Morán et al, 2017;Tian et al, 2020). Considering the actual clinical situations, patients usually take medications of XXMD in the poststroke (Pan et al, 2017;Zhong et al, 2020); we study the effect of components in treating stroke-based PC12 cells in the case that cells were protected with components after OGD. During the OGD, the cells were incubated in the culture medium without FBS in a hypoxic bag at 0.1% O 2 , 5% CO 2 , and 37 °C for 18 h (Gu et al, 2013;Morán et al, 2017).…”
Section: Oxygen and Glucose Deprivation Protocolmentioning
confidence: 99%
“…After administration, vanillic acid distributes mainly to liver and kidney, with trace amounts in the brain. 23 It was determined in another rat study 24 that the absorption and elimination of vanillic acid can be affected by the health condition of the rat. In light of these reports, a detailed characterization of the metabolism of vanillin and vanillic acid in the human GI tract and subsequent tissue distribution of metabolites are needed, especially as an important complement to future clinical studies.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Therefore, it is important to develop a method for the determination of vanillic acid in rat plasma. Literature research suggested that many analytical methods including HPLC (Xu et al, 2007) and LC-MS/MS (Bhutani et al, 2018;Du et al, 2017;Pan et al, 2017;Pang et al, 2016;Tao et al, 2019;Zeng et al, 2016) have been established and applied for the quantitative analysis of vanillic acid. However, these works mainly focused on the pharmacokinetic behavior of vanillic acid after oral administration of Chinese herb extracts.…”
Section: Introductionmentioning
confidence: 99%